Simulation of the injection of carbon dioxide into the oil reservoir. (Journal of Mathematics Mechanics and Computer Science, 2012)
In given article three-dimensional problem of two-phase mixture filtration,consisting of three components, one of them is dioxide carbon, is considered. The problem describes process of dioxide carbon injection to oil stratum.Computational algorithm for solving this problem is constructed.
Keywords: фильтрация; углекислый газ; светлые компоненты нефти; тяжелые компоненты нефти; пласт; неявная схема; прогонка